MARKETING MIX STRATEGY ANALYSIS ON COMPETITIVE ADVANTAGE OF SMALL AND MEDIUM ENTERPRISES (SME) AT UD SANJAYA DRY NOODLES - Meyrani Ananta Putri; M. Oktaviannur (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
The business sector in Indonesia has developed from the use of complex strategies, competition, change and uncertainty. The goal is to find out the implementation that must be carried out in order to compete in the global market. Especially in Natar District, South Lampung Regency, Lampung Province at UD Sanjaya Dry Noodle SMEs. The advantages possessed by UD Sanjaya are having quality ingredients, modern production equipment and having a variety of snack products. Marketing mix is ​​a marketing strategy that has seven elements (7P) in the form of products, prices, promotions, distribution, processes, officers and physical support that aim to achieve organizational goals. This study uses a qualitative descriptive approach. Qualitative research is a type of research that aims to understand and analyze a phenomenon, problem. This method focuses on collecting data such as interviews, observations, field notes, and document analysis to provide a clear and comprehensive picture of the situation or context at the time of the study. It can be concluded from the (7P) studied that promotions on social media can also increase UD Sanjaya's marketing targets.